Спекание нанопорошков тетрагонального диоксида циркония. Механизмы спекания и роль механического измельчения - Лакуста, М.В.; Даниленко, И.А.; Константинова, Т.Е.; Волкова, Г.К.; Глазунова, В.А. (Физика и техника высоких давлений, 2016)
The kinetics of the initial stage of sintering of two kinds of tetragonal zirconia nanopowders: 3Y-TZP, DIPE (ZrO₂–3 mol% Y₂O₃) (produced at DonIPE of NASU) and the TZ-3Y nanopowder similar in chemical composition (Tosoh, Tokyo, Japan) has been studied. To be analyzed, the 3Y-TZP nanopowders were obtained by the chemical coprecipitation method with mechanical grinding for 48 h (3Y-TZP-48M) and without grinding (3Y-TZP); the TZ-3Y nanopowders were obtained by the industrial hydrolysis. The shrinkage of the samples at the initial sintering stage was investigated at a constant rate of heating. After the processing of the dilatometric data, it was found that the 3Y-TZP nanopowders were sintered by the volume diffusion mechanism and the TZ-3Y nanopowders were sintered by the grain boundary diffusion mechanism. It was shown that the mechanical activation of nanopowders reduced the aggregation degree, resulted in a change of the phase composition and had a significant influence on the sintering mechanisms at the initial sintering stage.